Evidence-based Practice and Information and Communication Technology: Stakeholders’ Insights - Fajarini, Melati; Rahayu, Sri; Setiawan, Agus (Universitas Muhammadiyah Surakarta, 2022)
Stakeholders’ role to support evidence-based practice (EBP) and enhance the use of information and communication technology (ICT) for EBP is essential. However, how EBP is supported and how ICT is utilized in health care providers is unknown. Aim: This study aims to explore stakeholders’ insights regarding the implementation of EBP and the use of ICT. A qualitative study with the semi-structured face-to-face interview was used to obtain the aim. Using purposive sampling, eleven management representatives from public and private hospitals, clinics, and health offices in Depok city, Indonesia were asked about EBP and ICT. Data were recorded, transcribed, and analyzed thematically. Five themes emerged from this study. EBP services availability and accessibility showed ICT sources were adequate, but still need improvement in the library and Education and Training Department (ETD); Healthcare workforce represented doctors and nurses who hardly generate research although permitted by the stakeholders; Health information systems such as clinical cases forums in hospitals were established, but current evidence was rarely discussed; Funding for research and training related to EBP were not allocated; Leadership and governance showed there were limited policies on EBP and clinical instructors available in hospitals but focused on supporting training and student practices. Although EBP implementation needs improvement, the stakeholders in this study mostly support EBP and enable ICT for EBP purposes. Advocacy on policy and resource arrangements is urged to support information initiatives.